A pathogen-derived resistance strategy for the broad-spectrum control of grapevine leafroll-associated virus infection - Freeborough, Michael-John, 1971- (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2003.